Quantification and Localization of Formylated Phloroglucinol Compounds (FPCs) in Eucalyptus Species - Santos, Bruna Marques dos; Zibrandtsen, Juliane F. S.; Gunbilig, Disan; Sørensen, Mette; Cozzi, Federico; Boughton, Berin A.; Heskes, Allison Maree; Neilson, Elizabeth Heather Jakobsen (Frontiers in Plant Science, 2019)
The Eucalyptus genus is a hyper-diverse group of long-lived trees from the Myrtaceae family, consisting of more than 700 species. Eucalyptus are widely distributed across their native Australian landscape and are also the most widely planted hardwood forest trees in the world. The ecological and economical success of Eucalyptus trees is due, in part, to their ability to produce a plethora of specialized metabolites, which moderate abiotic and biotic interactions. Formylated phloroglucinol compounds (FPCs) are an important class of specialized metabolites in the Myrtaceae family, particularly abundant in Eucalyptus. FPCs are mono- to tetra-formylated phloroglucinol based derivatives, often with an attached terpene moiety. These compounds provide chemical defense against herbivory and display various bioactivities of pharmaceutical relevance. Despite their ecological and economical importance, and continued improvements into analytical techniques, FPCs have proved challenging to study. Here we present a simple and reliable method for FPCs extraction, identification and quantification by UHPLC-DAD-ESI-Q-TOF-MS/MS. The method was applied to leaf, flower bud and flower samples of nine different eucalypt species, using a small amount of plant material. Authentic analytical standards were used to provide high resolution mass spectra and fragmentation patterns. A robust method provides opportunities for future investigations into the identification and quantification of FPCs in complex biological samples with high confidence. Furthermore, we present for the first time the tissue-based localization of FPCs in stem, leaf and flower bud of Eucalyptus species measured by mass spectrometry imaging, providing important information for biosynthetic pathway discovery studies and for understanding the role of those compounds in planta.